Pemilihan Kazakhstan Sebagai Mitra Kerjasama China Dalam Sektor Energi Minyak Tahun 2003-2010 - Primadiana Yunita (Department of International Relations, Brawijaya University, 2015)
Abstract China’s economic growth is in parallel correspondence with its energy needs level. Consequence that showed up subsequently is increasing demand in energy source in China, thus China must provide adequate energy source for its industrial interest. Therefore, China has tried several strategies such as by cooperating with Kazakhstan. The objective of research is to figure out why China chooses Kazakhstan as the cooperation partner in the oil energy field during Hu Jintao government in the period 2003-2010. This research shows that the political economy cooperation between China Kazakhstan represents an effort for China to preserve the supply of domestic energy in order to facilitate economic growth. In this research, author used rational model theory, managed multi dependence concept. Method used in this research is explanation through literature study obtained from books, journals and articles related with this research theme. Keywords : external transformation, Regional Security Complex Theory, South China Sea Conflict